The Impact of Basic English Proficiency on the Academic Performance of Information Technology Students - Jong, Jek Siang; Nainggolan, Friska Fajrina; Susyetina, Arida (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
The Faculty of Information Technology at a private university in Yogyakarta offers two study programs: Informatics and Information Systems. To enhance students' English proficiency, all first-semester students are required to participate in the Introduction to College English (ICE) program, which comprises levels 1, 2, 3, before taking the English for Specific Purposes (ESP) course. A placement test is administered before the start of the first semester to determine students’ initial English proficiency level. This study examines the relationship between students' basic English skills—measured by their ICE placement level—and their academic performance, represented by their first-semester Grade Point Average (IPS). An ANOVA test was conducted on a dataset of 998 students from 2017 to 2021 to determine the significance of this relationship, followed by a Pairwise t-test to identify specific proficiency levels that contributed to significant differences in IPS scores. Data preprocessing steps included cleaning, integration, reduction, and transformation. The ANOVA results revealed a strong correlation between English proficiency and academic achievement, with a p-value (PR > F) of 0%. The Pairwise t-test results indicated that the most significant differences in IPS scores were observed between students with low English proficiency (level 1) and those with higher proficiency (level 3 or ESP). These findings highlight the critical role of English language skills in the academic success of Information Technology students.